Challenges Facing the BAZNAS Kendal Regency Microfinance Program in Building the Community’s Economy - Ahmad Solekhan (Journal of Management, Entrepreneurship, and Tourism, 2026)
The BAZNAS Micro Finance Program is a form of productive zakat implementation aimed at empowering mustahik through the provision of business capital, mentoring, and entrepreneurial development, with the expectation of serving as an effective Islamic economic empowerment instrument in reducing poverty, increasing community income, and strengthening economic independence. This study aims to analyze the implementation of the BAZNAS Micro Finance Program in Kendal Regency, identify the challenges encountered, and examine its role in strengthening the community economy. A qualitative method with a descriptive approach was employed, with data collected through interviews, observations, and documentation involving program managers, field facilitators, and beneficiaries, and analyzed using an interactive model of data condensation, data display, and conclusion drawing, supported by source and method triangulation to ensure data validity. The findings reveal that the program is implemented through beneficiary selection, productive capital distribution, business mentoring, and monitoring of mustahik business development, contributing positively to income improvement and business strengthening, although it is constrained by limited funding, insufficient mentoring capacity, suboptimal monitoring systems, underdeveloped evaluation frameworks, low financial literacy, limited managerial capacity, and dynamic market conditions.